"The effectiveness of a play-based training program for developing and preparing arithmetic readiness skills among a sample of kindergarten children in Zliten city." - Haniya Ahmed Abuasheiba; Mohamed Farag Salem Belayed; Mawada Naji Belaid (Journal of Scientific and Human Dimensions, 2026)
This study aimed to examine the effectiveness of a play-based training program in developing and preparing mathematical readiness among a sample of kindergarten children in the city of Zliten.The study adopted a quasi-experimental approach using a pre-test and post-test design for two groups (experimental and control). The study sample consisted of (40) children who were equally divided into two groups.The study population consisted of children from Al-Bara’ah Kindergarten in Zliten (Eastern Branch), from which the sample was selected.A play-based training program was implemented for the experimental group, while the control group did not receive the program. Pre- and post-tests were used to measure the level of mathematical readiness skills, in addition to a questionnaire as a supporting data collection tool.  The results revealed the following:There were statistically significant differences between the pre-test and post-test in favor of the post-test, indicating the effectiveness of the play-based training program in developing mathematical readiness skills among kindergarten children.There were no statistically significant differences between the two groups in the post-test, indicating an overall improvement in the children’s performance.These findings confirm the importance of using play as an effective educational method in early childhood.
Keywords: Psychological Depression; its Relationship to Academic Achievement; Practical Education Course; Faculty of Education; Al-Asmariya Islamic University; Zliten